INFORMASI LABA AKUNTANSI DAN ARUS KAS SERTA PENGARUHNYA PADA HARGA SAHAM - Susan, Marcellia (Jurnal Keuangan dan Perbankan, 2009)
The purpose of this research was to investigate whether publication andannouncement of accounting profit and cash flow could be considered as drivers of stockprice. The result of this research showed that accounting profit announcement could influencethe stock price of telecommunication companies. The result also indicated that stock price wasinfluenced by the interaction between accounting profit and cash flow from investment.